Probiotics in Disease Management for Sustainable Poultry Production - Gelana Urgesa Ayana; Robert Kamutambuko (Advanced Gut & Microbiome Research)
Probiotics have emerged as a viable strategy to mitigate diseases in poultry, offering a sustainable alternative to traditional methods. Therefore, this review explores the potential of probiotics to improve poultry health, productivity, and environmental impact within poultry farming systems. In the context of sustainable poultry production, the use of probiotics for disease management presents a promising avenue to improve animal health and productivity. This review provides a comprehensive analysis of the scientific rationale behind probiotic interventions in poultry, highlighting their ability to modulate the gut microbiota, enhance immune function, and mitigate pathogen proliferation and the mechanisms by which probiotics influence poultry health. Through a comprehensive review of the current literature and research findings, this review elucidates the potential of probiotics as a viable alternative to conventional antibiotic use to promote sustainable poultry production practices. By shedding light on the scientific rationale and practical applications of probiotics in disease management, this review contributes to a deeper understanding of how probiotic interventions can optimize poultry health outcomes while ensuring long-term sustainability in the poultry industry. This comprehensive review provides valuable information on the potential of probiotics as alternatives to antibiotics in poultry production and offers directions for future research and development in this field in formulations and metagenomic analysis. These studies present exciting opportunities for advancing the field of probiotics in poultry production.